The Hospital Claims of HIV/AIDS Inpatient at Working Area of BPJS Kesehatan Cabang Mojokerto - Sihombing, Gustina Fajarwati; Meliala, Andreasta (BPJS Kesehatan, 2024)
This study aims to see and analyze the inpatient claims of Human Immunodeficiency Virus/ Acquired Immunodeficiency Syndrome at Mojokerto Hospitals. The research design used is a type 2 case study, namely an embedded single case and uses a qualitative approach. The results of the study show that the largest proportion of HIV/AIDS inpatient JKN patients is the type of Beneficiaries of Contribution Assistance (PBI) membership which is a segment of the underprivileged community. Until now, the Global Fund still contributes significantly to the efforts of the Indonesian government in terms of spending on HIV/AIDS programs. The Indonesian government has not yet had any serious regulations and efforts that lead to optimizing financing independently.